1k+23/9=8

Simple and best practice solution for 1k+23/9=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1k+23/9=8 equation:



1k+23/9=8
We move all terms to the left:
1k+23/9-(8)=0
determiningTheFunctionDomain 1k-8+23/9=0
We add all the numbers together, and all the variables
k-8+23/9=0
We multiply all the terms by the denominator
k*9+23-8*9=0
We add all the numbers together, and all the variables
k*9-49=0
Wy multiply elements
9k-49=0
We move all terms containing k to the left, all other terms to the right
9k=49
k=49/9
k=5+4/9

See similar equations:

| 85=5(k-64) | | 3x-5+85=90 | | 2(b+12=36 | | 17=c4+ 14 | | (3x-3)+42=90 | | 2/5(10x+5)=20 | | 17=c/4+ 14 | | 8=2b+6 | | x3/8=24 | | 11x-29=24x=101 | | -(x+7)-5=4(x+3) | | -7x+5(x-3)=-1 | | 471=v−31 | | 7c+16=-9 | | 10x+33=17x+37 | | 19q=665 | | s−48=41 | | 47+6=b | | 6(x-5)2=54 | | 25=-8+9x+3 | | s=43+19 | | 5(15x+100)=1025 | | 1-5y=10 | | 22+x=4*8x | | -5=-x-2 | | x*40=75 | | 6+2r=2 | | -5(10c-14)=14(8-4c) | | 12p-4=10p+5-6p | | -5(10c-14)=149-4c | | 4(x+3)=4(-x-1) | | (z−5)(9z+4)=0 |

Equations solver categories